DIGITAL SOCIAL INNOVATION AND LABOR MARKET TRANSFORMATIONS - Marzano, Gilberto (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Social innovation can be considered as a process generated by the application of innovation to social needs. Consequently, digital social innovation (DSI) addresses emerging social issues and challenges by taking advantage of digital technology.Currently, most DSI projects make use of more established - and less ‘high-tech’ - solutions, such as social networks, crowdsourcing, and web or mobile apps.Indeed, there is a large pool of people with great ideas, but without the digital skills to bring their ideas to life. A great effort is needed to enable people to access digital skills.This paper highlights how DSI education can contribute, in a period of transformation of the labor market, to enhancing solutions in several strategic sectors, such as healthcare, education, public participation, and the environment.It presents the results of the EU funded project DSI: new educational competences for social inclusion (2018-2020) whose aim is the definition of a basic portfolio of competences for social educators and social volunteers in DSI at a European level.